The electrical impedance measurements of dry electrode materials for the ECG measuring after repeated washing. (13th March 2017) - Kaappa, Emma Sofia; Joutsen, Atte; Cömert, Alper; Vanhala, Jukka
Abstract : Purpose: The purpose of this paper was to offer more reliable dry electrode materials for long-term measuring and determine how repeated machine washing affects the measured impedance and surface resistance of the sample electrodes. The aim was to manufacture electrodes that could be used for the measurement of ECG. Skin friendly, metal sheet type, electrodes could be a solution. Design/methodology/approach: In addition to two conventional electrodes already used in heart rate belts, the authors prepared and tested three different sheet metal electrodes. Three 20-mm-diameter electrodes were manufactured from the following materials: silvered knit, conductive polymer, stainless steel, silver and platinum. Electrode impedance was measured at seven frequencies from 1 Hz to 1 MHz, by placing two electrodes face-to-face. Measurements were taken on unused electrodes and after multiple machine washes at 40°C. Findings: Analysis of the measurements indicates that with every material tested, the impedances are elevated after repeated washes. All metallic materials have impedances in the range of 0.01 to 4.5 Ω. Metal sheet electrodes can be integrated comfortably into the textile, and they endure textile maintenance without loss of electrical properties. Practical implications: Metal sheet electrodes function well in long-term vital signs monitoring, provide a reliable signal and are resistant to maintenance. For the reasons described in this research, they can be used as a long-term wearable sensor. Originality/value: Novel electrode material for long-term measuring research is important in many disciplines such as health care and apparel manufacturing. These findings suggest that pure metal electrodes are better than conductive textiles in long-term measuring.